Peran Pondok Pesantren dalam Membentuk Kemandirian Belajar Santri Brokenhome - Maulana, M. Irsyad; Sobiroh, Novi Ismi (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: Islamic boarding schools, as religious-based educational institutions, have an important role in forming the character and independence of students. This research aims to reveal the extent to which Islamic boarding schools can become a "second home" for brokenhome students and how the Islamic boarding school environment contributes to shaping their learning independence. Using a descriptive qualitative approach, the researcher took the research focus at the Queen Assalam Islamic Boarding School Sumber Beras Banyuwangi which has several broken-home students. Data collection techniques use observation, interviews and documentation from data sources, namely kyai, administrators and students. The data was then analyzed using three stages, namely data condensation, data presentation, and drawing conclusions. The results of this research state that the role of Islamic boarding schools is manifested in the role of Kyai and caregivers in internalizing the values of independent learning in students. This role takes the form of an educator, mentor and motivator. This is supported by factors that influence the development of their learning independence so that the process can be more effective and efficient. Abstrak: Pondok pesantren, sebagai lembaga pendidikan berbasis agama, memiliki peran penting dalam membentuk karakter dan kemandirian santri. Penelitian ini bertujuan untuk mengungkap sejauh mana pondok pesantren dapat menjadi "rumah kedua" bagi santri brokenhome dan bagaimana lingkungan pesantren berkontribusi dalam membentuk kemandirian belajar mereka. Melalui pendekatan kualitatif deskriptif, peneliti mengambil lokus penelitian di Pondok Pesantren Queen Assalam Sumber Beras Banyuwangi yang memiliki beberapa santri brokenhome. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi dari sumber data, yakni kyai, pengurus dan santri. Data kemudian dianalisis dengan menggunakan tiga tahapan, yakni kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menyebutkan bahwa peran pondok pesantren diwujudkan pada peran Kyai dan pengasuh dalam menginternalisasikan nilai-nilai kemandirian belajar pada santri. Peran tersebut berupa peran sebagai pendidik, pembimbing dan motivator. Hal ini didukung dengan faktor-faktor yang mempengaruhi perkembangan kemandirian belajar mereka sehingga proses yang dijalani bisa lebih efektif dan efisien